Dextrocardia–value of segmental analysis in its categorisation. Issue 5 (November 1979) - Calcaterra, G; Anderson, R H; Lau, K C; Shinebourne, E A
Abstract : Dextrocardia can be defined as a heart in the right chest with the major axis to the right. This definition, however, conveys no information regarding the chamber arrangements and internal anatomy of the heart. Of 40 patients satisfying this definition in the files of the Brompton Hospital, 33 had angiocardiographic data adequate for complete analysis in terms of connections, relations, and morphology of cardiac segments. They form the subject of this report. There were 16 (48%) patients with situs solitus, 11 (33%) with situs inversus, and six (18%) with situs ambiguus. Of the cases of situs ambiguus, four exhibited laevoisomerism and two dextroisomerism. Of the 16 patients with situs solitus, six had two ventricles and 10 had univentricular hearts; two patients had concordant and three discordant ventriculoarterial connections, seven had double outlet ventricle, and four a single outlet heart. Of the 11 patients with situs inversus, nine had two ventricles and two a univentricular heart of right ventricular type; the arterial connection was concordant in two, discordant in two, double outlet in six, and single outlet in one. Of the six patients with situs ambiguus and laevo or dextroisomerism, four had two ventricles, and two univentricular hearts; the arterial connection was concordant in one, double outlet in three, and single outlet in two. Segmental analysis and the use of basic descriptive terms are essential to define the complex anatomy of such hearts.